Consumption of Diet Containing Free Amino Acids Exacerbates Colitis in Mice - Souza, Adna Luciana; Fiorini Aguiar, Sarah Leão; Gonçalves Miranda, Mariana Camila; Lemos, Luisa; Freitas Guimaraes, Mauro Andrade; Reis, Daniela Silva; Vieira Barros, Patrícia Aparecida; Veloso, Emerson Soares; Carvalho, Toniana Gonçalves; Ribeiro, Fabiola Mara; Ferreira, Enio; Cara, Denise Carmona; et al. (Frontiers in Immunology, 2017)
Dietary proteins can influence the maturation of the immune system, particularly the gut associated lymphoid tissue (GALT), when consumed from weaning to adulthood. Moreover, replacement of dietary proteins by amino acids at weaning has been shown to impair the generation of regulatory T cells in the gut as well as immune activities such as protective response to infection, induction of oral and nasal tolerance as well as allergic responses. Polymeric and elemental diets are used in the clinical practice, but the specific role of intact proteins and free amino acids during the intestinal inflammation are not known. It is plausible that these two dietary nitrogen sources would yield distinct immunological outcomes since proteins are recognized by the immune system as antigens and amino acids do not bind to antigen-recognition receptors but instead to intracellular receptors such as mTOR. In this study, our aim was to evaluate the effects of consumption of an amino-acid-containing diet versus a control protein-containing diet in adult mice at steady state and during colitis development. We showed that consumption of a diet containing free amino acids (AA diet) by adult mature mice lead to various immunological changes including decrease in the production of serum IgG as well as increase in the levels of IL-6, IL-17A, TGF-β and IL-10 in the small and large intestines. It also led to changes in the intestinal morphology, to increase in intestinal permeability, in the number of total and activated CD4+ T cells in the small intestine as well as in the frequency of proliferating cells in the colon. Moreover, consumption of AA diet during and prior to development of DSS-induced colitis exacerbated gut inflammation. Administration of rapamycin during AA diet consumption prevented colitis exacerbation suggesting that mTOR activation was involved in the effects triggered by the amino-acid-containing diet. Therefore, our study suggests that different outcomes can result from the use of diets containing either intact proteins or free amino acids such as elemental, semi elemental and polymeric diets during intestinal inflammation. These results may contribute to the design of nutritional therapeutic intervention for inflammatory bowel diseases.